Synthesis and characterization of nitrogen-doped-MWCNT@cobalt oxide for nerve agent simulant detection - Sanjeeb Lama; Hyeong-Seon Choi; Sivalingam Ramesh; Young Jun Lee; Joo Hyung Kim (Scientific Reports, 2024)
Abstract Organophosphorus nerve agents are toxic compounds that disrupt neuromuscular transmission by inhibiting the neurotransmitter enzyme, acetylcholinesterase, leading to rapid death. A hybrid composite was synthesized using a hydrothermal process for the early detection of dimethyl methyl phosphonate (DMMP), a simulant of the G-series nerve agent, sarin. Quartz crystal microbalance (QCM) and surface acoustic wave (SAW) sensors were used as detectors. Nitrogen-doped multiwalled carbon nanotubes (N-MWCNTs), cobalt oxide (Co3O4), and N-MWCNT@Co3O4 were compared to detect DMMP concentrations of 25–150 ppm. At 25 ppm, the differential frequencies (Δf) of the N-MWCNT, Co3O4, and N-MWCNT@Co3O4 sensors were 5.8, 2.3, and 99.5 Hz, respectively. The selectivity results revealed a preference for the DMMP rather than potential interference. The coefficients of determination (R2) of the N-MWCNT, Co3O4, and N-MWCNT@Co3O4 sensors for detecting 25–150 ppm DMMP were 0.983, 0.986, and 0.999, respectively. The response times of the N-MWCNT, Co3O4, and N-MWCNT@Co3O4 sensors for detecting 100 ppm DMMP were 25, 27, and 34 s, respectively, while the corresponding recovery times were 85, 105, and 181 s. The repeatability results revealed the reversible adsorption and desorption phenomena for the fixed DMMP concentration of 100 ppm. These unique findings show that synthesized materials can be used to detect organophosphorus nerve agents.